Isatin/thiosemicarbohydrazone hybrids: Facile synthesis, and their evaluation as anti-proliferatıve agents and metabolıc enzyme inhibitors - Hasan Yakan; Mohammed Azam; Sevgi Kansız; Halit Muğlu; Mustafa Ergül; Parham Taslimi; Koçyiğit, Ümit M.; Muhammet Karaman; Al-Resayes, Saud I.; Kim Min (African Journals Online (AJOL), 2023)
ABSTRACT. We are reporting a novel series of thiosemicarbazone derivatives derived from isatin (1-6), structural determination, and investigation of the inhibitory properties against proliferative, carbonic anhydrase, and cholinesterase enzymes. The anti-proliferative effects of the compounds were measured by XTT assay against MCF-7 and MDA-MB-231 cancerous cell lines. Compound 3 showed significant cytotoxic effects on both MCF-7 and MDA-MB-231 cell lines, with IC50 values of 8.19 μM and 23.41 μM, respectively. In addition, the compounds (1-6) inhibited the hCA I and II, their Ki values 2.01 ± 0.35 – 21.55 ± 2.56 and 1.24 ± 0.33 – 25.03 ± 5.48 µM, respectively. AChE was also successfully inhibited by these compounds (1-6), with Ki values ranging from 40.37 ± 8.23 to 125.43 ± 24.93 µM. The best Ki values for 3, 6, and 4 for α-glycosidase were 564.35 ± 72.06, 594.38 ± 52.04, and 683.437 ± 66.58 µM, respectively. Binding affinities were determined to be -6.697 kcal/mol, -8.251 kcal/mol, -9.932 kcal/mol, and -4.946 kcal/mol for hCA I, hCA II, AChE, and α-glucosidase enzymes, respectively. These findings reveal that the formed compounds containing isatin moieties were crucial in the enzyme inhibition.

KEY WORDS: Isatin, Thiosemicarbazone, Anti-proliferative activity, Enzyme inhibition, Molecular docking

Bull. Chem. Soc. Ethiop. 2023, 37(5), 1221-1236.
DOI: https://dx.doi.org/10.4314/bcse.v37i5.14
Keywords: Isatin; Enzyme inhibition; Isatin, Thiosemicarbazone, Anti-proliferative activity, Enzyme inhibition, Molecular docking; Enzyme Inhibition; Molecular docking; Anti-Proliferative Activity; Thiosemicarbazone; Anti-proliferative activity; Molecular Docking; 3. Good health